An investigation into partial capture of CO2 released from a large coal/petcoke fired circulating fluidized bed boiler with limestone injection using its fly and bottom ash. Issue 1 (February 2017) - Patel, Anantkumar; Basu, Prabir; Acharya, Bishnu
Abstract: Circulating Fluidized Bed (CFB) power plants have been gaining popularity globally due to its ability to utilize less expensive solid fuels, in-situ capture of SOx, low NOx emission and flexible operating characteristics. Higher CO2 emission from sulfur capturing CFB plants is, however, a major shortcoming of this technology. Additionally, fly ash generated from such CFB power plants is not favorable for many commercial applications. This work examined if the fly ash produced in a CFB power plants with limestone feed can capture a part of the CO2 released from it. It studied factors affecting capture of CO2 utilizing by its ash. Two sets of experiments were carried out for dry and hydrated fly ash at 500–750 °C and 30–80 °C respectively. Tests showed that CaO conversion increased with temperature up to 700 °C for the dry case and 50 °C for hydrated case thereafter it started to reduce. Effect of partial pressure of CO2 (17 kPa–31 kPa) on the total carbonation reaction was minor, but, the duration of initial rapid CO2 capture stage was inversely proportional to the CO2 partial pressure. For benchmarking the capture characteristics of lime were compared with that of CFB ash at the same conditions. In most cases carbonation reaction in lime followed a similar pattern as in fly ash. The capture characteristics were also similar for bottom ash (particle size, 116 μm–275 μm). However, the amount of CO2 captured by the coarser bottom ash was significantly lower than that by dry fly ash at the same condition. This study, thus showed the potential of using fly ash from sulfur capturing CFB power plants in reducing the CO2 emission from the very plant and thereby achieve better disposal of the fly ash.